Sistem Pendukung Keputusan Pemilihan Produk Promo Dengan Menggunakan Metode Analytical Hierarchy Process - Simple Additive Weighting (AHP - SAW) (Studi Kasus : Geprek Kak Rose) - Royan Krisnanda Tiony; Niken Hendrakusma Wardani; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Decision making on a product must be taken appropriately and in line with company's objectives so that a business will have a long product life cycle and win the market competition. One form of decision making undertaken by a company is through the process of Decision Support System (DSS). The DSS implementation in the culinary business Geprek Kak Rose will help the company in decision making process related to products promotion recommendation to be more accurate and faster to make the company reach target and stay competitive. In determining the product promotion, the company uses a number of criteria that are used as references such as Price, Sales, Durability, and Inventory. These criteria will be the main guideline in DSS using the AHP (Analytical Hierarchy Process) - SAW (Simple Additive Weighting) method. AHP method is used for the criteria weighting process, then proceed with the SAW method for the best performance ranking process based on all available alternatives. To see the suitability of DSS made with a manual decision from the user, this study uses a Spearman correlation test that produces a value of 0.737 which means it has a very strong relationship.